2023
DOI: 10.1186/s12870-023-04617-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of WUSCHEL-related homeobox gene and truncated small peptides in transformation efficiency improvement in Eucalyptus

Zhuo-Ao Zhang,
Mei-Ying Liu,
Shu-Ning Ren
et al.

Abstract: Background The WUSCHEL-related Homeobox (WOX) genes, which encode plant-specific homeobox (HB) transcription factors, play crucial roles in regulating plant growth and development. However, the functions of WOX genes are little known in Eucalyptus, one of the fastest-growing tree resources with considerable widespread cultivation worldwide. Results A total of nine WOX genes named EgWOX1-EgWOX9 were retrieved and designated from Eucalyptus grandis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Supported by the conserved motifs and intron patterns, the highly conserved gene structure guarantees the conserved function of each clade or subclade. WOX genes in the same subfamily tend to have similar numbers of introns and exons, and they also share similarities in gene structure (Figure 3) [50,51]. The gene of the ancient clade has a more conserved gene structure than the other two clades' genes, consistent with the WOX genes of Arabidopsis, Poplar, and Sorghum [37].…”
Section: Discussionmentioning
confidence: 61%
“…Supported by the conserved motifs and intron patterns, the highly conserved gene structure guarantees the conserved function of each clade or subclade. WOX genes in the same subfamily tend to have similar numbers of introns and exons, and they also share similarities in gene structure (Figure 3) [50,51]. The gene of the ancient clade has a more conserved gene structure than the other two clades' genes, consistent with the WOX genes of Arabidopsis, Poplar, and Sorghum [37].…”
Section: Discussionmentioning
confidence: 61%
“…The root development of woody plants is a very complex process. Hence, it is crucial to understand the molecular mechanisms underlying primordial, lateral, and adventitious roots to improve the efficiency of the root regeneration system in histoculture and to conduct an in-depth study of plant regeneration [4]. Numerous studies have revealed that the WOX gene family plays an important regulatory role in the critical period of plant rooting [5,6,[9][10][11][12][13]17].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the WOX family and endogenous cytokines and growth hormones play a key role in regulating the formation and maintenance of healing tissue. WOX11 is a key gene involved in growth hormone response and cell fate transition, and the expression of WOX11 transforms regeneration-competent cells into adventitious root founder cells [4,32]. The OsADA2-OsGCN5 complex was identified as a WOX11-interacting partner and was shown to activate the expression of downstream genes to maintain the cell division rate [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations